Genetic insights into smoking behaviours in 10,558 men of African ancestry from continental Africa and the UK - Noemi-Nicole Piga; Palwende Romuald Boua; Chisom Soremekun; Nick Shrine; Kayesha Coley; Jean-Tristan Brandenburg; Martin D. Tobin; Michèle Ramsay; Segun Fatumo; Ananyo Choudhury; Chiara Batini (Scientific Reports, 2022)
Abstract Smoking is a leading risk factor for many of the top ten causes of death worldwide. Of the 1.3 billion smokers globally, 80% live in low- and middle-income countries, where the number of deaths due to tobacco use is expected to double in the next decade according to the World Health Organization. Genetic studies have helped to identify biological pathways for smoking behaviours, but have mostly focussed on individuals of European ancestry or living in either North America or Europe. We performed a genome-wide association study of two smoking behaviour traits in 10,558 men of African ancestry living in five African countries and the UK. Eight independent variants were associated with either smoking initiation or cessation at P-value < 5 × 10–6, four being monomorphic or rare in European populations. Gene prioritisation strategy highlighted five genes, including SEMA6D, previously described as associated with several smoking behaviour traits. These results confirm the importance of analysing underrepresented populations in genetic epidemiology, and the urgent need for larger genomic studies to boost discovery power to better understand smoking behaviours, as well as many other traits.